2014
DOI: 10.1002/pmic.201400019
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of specific cellular defense proteins in rat hypothalamus under simulated microgravity induced conditions: Comparative proteomics

Abstract: Microgravity severely halts the structural and functional cerebral capacity of astronauts especially affecting their brains due to the stress produced by cephalic fluid shift. We employed a rat tail suspension model to substantiate simulated microgravity (SM) in brain. In this study, comparative mass spectrometry was applied in order to demonstrate the differential expression of 17 specific cellular defense proteins. Gamma-enolase, peptidyl-prolyl cis-trans isomerase A, glial fibrillary acidic protein, heat sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…The HSP70/90 heat shock proteins are known to be involved in the regulation of cell cycle progression and cell proliferation 44 , and increased expression of BIRC5 should result in less apoptosis that might be induced by microgravity stress. In other studies, up-regulation of heat shock proteins was also observed in rat hypothalamus tissues 45 , the Jurkat cells 46 and myelomonocytic U937 cells 47 as a result of exposure to microgravity, and BIRC5 was up-regulated in thymus after mice returned from a spaceflight 48 . In addition, a study on neonatal and adult cardiovascular progenitors reported that simulated microgravity could affect cell differently depending on age 42 .…”
Section: Discussionmentioning
confidence: 67%
“…The HSP70/90 heat shock proteins are known to be involved in the regulation of cell cycle progression and cell proliferation 44 , and increased expression of BIRC5 should result in less apoptosis that might be induced by microgravity stress. In other studies, up-regulation of heat shock proteins was also observed in rat hypothalamus tissues 45 , the Jurkat cells 46 and myelomonocytic U937 cells 47 as a result of exposure to microgravity, and BIRC5 was up-regulated in thymus after mice returned from a spaceflight 48 . In addition, a study on neonatal and adult cardiovascular progenitors reported that simulated microgravity could affect cell differently depending on age 42 .…”
Section: Discussionmentioning
confidence: 67%
“…For each experiment, ten rats were taken and divided into two groups. For SM, rats were kept suspending their bodies with their tails for 21 days as reported previously . The control rats were kept in normal cages with free access to food and water.…”
Section: Methodsmentioning
confidence: 99%
“…Earth-based simulation studies have been designed to investigate the physiological responses to microgravity. Tail suspension model has been widely used for the simulation of microgravity [7,15,[22][23][24][25][26][27][28] and approved by the National Aeronautics and Space Administration (NASA), Ames Research Center (ARC), and Institutional Animal Care and Use Committee on August 8, 2001 [29]. A variety of studies have investigated cognitive function under simulated microgravity (SM).…”
Section: Introductionmentioning
confidence: 99%